Systematics and Faunistics of Neotropical Olethreutini, 2: Episimus Walsingham, 1892 (Lepidoptera: Tortricidae) - J. Razowski; V. O. Becker (SHILAP, 2017)
Twelve species of Episimus Walsingham, 1892 are described and illustrated (E. granpiedrae Razowski & Becker, sp. n., E. meranus Razowski & Becker, sp. n., E. joaquimus Razowski & Becker, sp. n., E. eisniveus Razowski & Becker, sp. n., E. niveopictus Razowski & Becker, sp. n., E. serenus Razowski & Becker, sp. n., E. spinuliferus Razowski & Becker, sp. n., E. cubaenatus Razowski & Becker, sp. n., E. maricao Razowski & Becker, sp. n., E. caracanus Razowski & Becker, sp. n., E. niveogriseus sp. n., E. opponens Razowski & Becker, sp. n.), and distribution data on twelve other species are provided. Episimoides Diakonoff, 1957 is synonymized with Episimus and Afrotropical Episimoides erythraea Diakonoff, 1957 is transferred to Episimus.